SINGLE NUCLEOTIDE POLYMORPHISMS IN THE D-LOOP REGION OF THE MITOCHONDRIAL GENOMES OF INDIVIDUALS FROM TWO ETHNIC GROUPS KINH AND MANG OF AUSTRO-ASIATIC LANGUAGE FAMILY - Ngoc, Nguyen Thy; Trang, Nguyen Bao; Huy, Nguyen Quang; Ton, Nguyen Dang; Duong, Nguyen Thuy (Vietnam Journal of Biotechnology, 2018)
The two hypervariable regions HV-I and HV-II in the D-loop region are the most diverse region in the mitochondrial human genome. These DNA regions have an important role in population genetics and human evolution research. In this study, we identified single nucleotide polymorphisms (SNPs) in the D-loop region of the human mitochondrial DNA genomes of individuals in two Vietnamese ethnic groups: Kinh and Mang. 81 blood samples from 50 Kinh and 31 Mang unrelated individuals were collected for genomic DNA extraction. Using PCR and specific primers, we successfully amplified the two HV-I and HV-II regions with respective sizes of 693 bp and 689 bp. The PCR products then were purified and sequenced. After alignment to the reference mitochondrial genome rCRS (NC_012920.1), 96 SNPs were detected in the Kinh ethnic group, of which many polymorphisms were firstly found in this ethnic and 36 SNPs in the Mang ethnic group. Of the identified 132 SNPs, 16 SNPs were significantly different between the two ethnic groups (p < 0.05). Eight out of the 16 SNPs (T146C, T199C, A16182C, T16217C, T16297C, T16140C, A16183C, T16189C) were frequently found in the Kinh ethnic group but not or only rarely in the Mang ethnic group. On the other hand, 4 SNPs (C151T, A16162G, A16269G, T16271C) were commonly found in the Mang population but rarely in the Kinh population. These findings suggest that although Kinh and Mang belong to one language family (Austro-Asiatic), there is a noticeable diversity in the mitochondrial genomes between these two Vietnamese ethnic groups.